Beyond belief the American press and the coming of the Holocaust, 1933 - 1945 - Lipstadt, Deborah E. 1947- (Free Pr. u.a., 1986)
Examines the role of the American press in presenting the information known about the Jewish Holocaust during World War II to the American people in such a way that it fostered inaction and indifference.
Keywords: Geschichte 1933-1945; Holocaust; Holocauste, 1939-1945 - Opinion publique; Journaux américains; Juifs - Allemagne - Histoire - 1933-1945 - Opinion publique; Opinion publique - États-Unis; Perswezen; Geschichte; Juden; Judenvernichtung; American newspapers; Holocaust, Jewish (1939-1945) -- Public opinion; Jews -- Germany -- History -- 1933-1945 -- Public opinion; Public opinion -- United States; Presse; Judenverfolgung; Allemagne - Opinion publique américaine; Deutschland; USA; Germany -- Foreign public opinion, American